The Impact of Free Senior High School Education Policy on the Quality of Education in Ghana - Abdalla Adbul-Rahim; Dickson Adom; Joe Adu-Agyem (ASEAN Multidisciplinary Research Journal, 2022)
The purpose of the study was to assess the impact of the Free Senior High School (FSHS) Policy on the quality of education in Ghana using the case of the Kintampo Senior High School. This study adopted the convergent parallel mixed method approach to gather data for the research from 303 students, 97 teachers, 3 headmaster (including 2 assistants), 1 matron, and 2 officers from the Kintampo education directorate who were purposively and simple randomly sampled. Structured questionnaire and semi-structured interview guide were the main data collection instruments. The quantitative data were analysed using quantitative descriptive analysis with the help of the SPSS while the qualitative data were analysed using the qualitative thematic analysis. The findings of the study show significant improvement in education following the introduction of the FSHS policy. Tuition (84.26%), resources and other related fees (73.59%) are fully funded by the government. Students had the chance to pursue studies in the institution of their choice (60.32%). Also, student enrolment (87.45%), adequacy of teachers (84.21%) and academic performance (from 15% to 96.6%) has increased significantly. The few challenges noted were associated with large class sizes and the need for more expansions in the boarding facilities to accommodate the rising numbers in student enrolment. The study contends that the private sector should support the government by assisting in the provision of funding for the ever-increasing need of infrastructure in the various second cycle institutions in the country. Also, there is the need for an institutionalization of a quality education mechanism to regularly ensure that quality education is not compromise in the rollout of the FSHS policy.